Sustainability of three recreational forest landscape management in Selangor, Malaysia - Hussein, Mohd. Kher (Faculty of Built Environment, University of Malaya, 2014)
Different stakeholders managed recreational forests in Selangor, Malaysia. These stakeholders? involvements have risen a question whether their development have fulfilled the sustainable landscape requirement. The aim of this study was to understand and generate more comprehensive knowledge on the recreational forest landscape management towards forest sustainability. The objectives of this study were to evaluate the management of recreational forest in Selangor, Malaysia that affect landscape sustainability and to gain an overview of recreational forest landscape development in Peninsular Malaysia. The study applies three methods. First is the analysis of documents relating to sustainable landscape concept. Secondly, through case studies where three recreational forest sites in Selangor were selected to analyze their management practices towards landscape sustainability. Thirdly, field observations were carried out to collect data about existing physical conditions of the study sites. The results revealed that landscape management of these recreational forests were not in accordance with landscape sustainability approaches and needs improvement. This was caused by improper planning, low understanding among the staffs regarding sustainable landscape management, shortage of knowledgeable personnel, and poor supervision. Failure to adopt and implement sustainable landscape practices which include environment protection, social improvements, good governance, aesthetics enhancement, economy benefits, and harmonized designs can lead to the increase in the ?abandon syndrome? of some recreational forest sites in Peninsular Malaysia.